2020
DOI: 10.1029/2020gl089808
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Process for Northward Propagation of Boreal Summer Intraseasonal Oscillation Over the Western North Pacific

Abstract: Northward propagation of boreal summer intraseasonal oscillation (BSISO) over the Western North Pacific (WNP) has significant impacts on extreme events over Asia and Europe. Here we test hypotheses that northward propagation mechanisms over the WNP may differ from those over the Indian Ocean (IO) by performing numerical experiments with changing mean states through lowering the Tibetan Plateau (TP). Our results suggest that air-sea interaction plays a dominant role in the propagation over the WNP, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Note that the generation of negative SST anomalies (Figure 7h) can be attributed to the Rossby‐wave zonal winds in the previous pentads (pentad −2, Figure 7b), which induces positive evaporation anomalies (Figure 8) that cools the sea surface (Figure 7). Thus, it suggests that the northward propagation over WP is associated with the air‐sea interaction, consistent with the previous results on the northward propagation mechanism of the ISO over the WNP (Hsu & Weng, 2001; Liu & Wang, 2014; B. Wang & Zhang, 2002; T. Wang, Yang, et al., 2018; Yang et al., 2020).…”
Section: Diagnosis Of Moisture Tendency For Eastward and Northward Propagationsupporting
confidence: 91%
“…Note that the generation of negative SST anomalies (Figure 7h) can be attributed to the Rossby‐wave zonal winds in the previous pentads (pentad −2, Figure 7b), which induces positive evaporation anomalies (Figure 8) that cools the sea surface (Figure 7). Thus, it suggests that the northward propagation over WP is associated with the air‐sea interaction, consistent with the previous results on the northward propagation mechanism of the ISO over the WNP (Hsu & Weng, 2001; Liu & Wang, 2014; B. Wang & Zhang, 2002; T. Wang, Yang, et al., 2018; Yang et al., 2020).…”
Section: Diagnosis Of Moisture Tendency For Eastward and Northward Propagationsupporting
confidence: 91%
“…The enhancement of both warm SST and negative LHF anomaly facilitates creating low‐level cyclonic circulation and convergence. The northward propagation mechanisms in this study have shown to well follow the results revealed in previous studies (Jiang et al., 2004; Yang et al., 2020). All changes in air‐sea interaction processes, as well as dynamical processes, occur more distinctly in the E‐DV than in the E‐DC summers.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…The strong cyclonic circulation of these surface zonal wind anomalies over 0°-25°N are in good agreement with the characteristics of the relative vorticity over 5N°-15°N in Figure 5c. Besides, we can see the regressed pattern of surface zonal wind anomalies that strong easterlies to the north of the convection and westerlies within it in the western Pacific coincide with the development of warm and cold SST anomalies in Figures Many studies (Jiang et al, 2004;Kemball-Cook & Wang, 2001;Yang et al, 2019Yang et al, , 2020 have mentioned that the SST distribution, as well as the mean flow, has a strong effect on the character of the BSISO convection. In Figure 5f, we examine the role of air-sea interaction in the northward propagation of convection in the western Pacific for E-DV and E-DC summers.…”
Section: Mechanisms For Driving Different Northward Propagation Betwe...mentioning
confidence: 80%
See 1 more Smart Citation
“…A body of literature exists on the studies of BSISO simulation (e.g., Waliser et al, 2003b;Li and Mao, 2016;Hu et al, 2017;Yang et al, 2020). In general, most climate models continue to underestimate the intraseasonal variability of the BSISO and associated monsoon variability.…”
Section: Introductionmentioning
confidence: 99%